Effectiveness of 7-Valent Pneumococcal Conjugate Vaccine Against Invasive Pneumococcal Disease in Medically At-Risk Children in Australia: A Record Linkage Study. Issue 9 (30th May 2022) - Kabir, Alamgir; Newall, Anthony T; Randall, Deborah; Moore, Hannah C; Jayasinghe, Sanjay; Fathima, Parveen; Liu, Bette; McIntyre, Peter; Gidding, Heather F
Abstract: Background: Children with chronic medical conditions are at higher risk of invasive pneumococcal disease (IPD), but little is known about the effectiveness of the primary course of pneumococcal conjugate vaccine (PCV) in these children. Methods: A cohort born in 2001–2004 from two Australian states and identified as medically at-risk (MAR) of IPD either using ICD-coded hospitalizations (with conditions of interest identified by 6 months of age) or linked perinatal data (for prematurity) were followed to age 5 years for notified IPD by serotype. We categorized fully vaccinated children as either receiving PCV dose 3 by <12 months of age or ≥1 PCV dose at ≥12 months of age. Cox proportional hazard modeling was used to estimate hazard ratios (HRs), adjusted for confounders, and vaccine effectiveness (VE) was estimated as (1-HR) × 100. Results: A total of 9220 children with MAR conditions had 53 episodes of IPD (43 vaccine-type); 4457 (48.3%) were unvaccinated and 4246 (46.1%) were fully vaccinated, with 1371 (32.3%) receiving dose 3 by 12 months and 2875 (67.7%) having ≥1 dose at ≥12 months. Estimated VE in fully vaccinated children was 85.9% (95% CI: 33.9–97.0) against vaccine-type IPD and 71.5% (95% CI: 26.6–88.9) against all-cause IPD. Conclusion: This is the first population-based study evaluating the effectiveness of PCV in children with MAR conditions using record linkage. Our study provides evidence that the VE for vaccine-type and all-cause IPD in MAR children in Australia is high and not statistically different from previously reported estimates for the general population. This method can be replicated in other countries to evaluate VE in MAR children. Abstract : This population-based retrospective cohort study estimated that the 7-valent pneumococcal conjugate vaccine was highly effective against vaccine-type (91.1%) and all-cause (82.5%) invasive pneumococcal disease in children with medically at-risk conditions in Australia.